APPLICATION OF THE SIMPLE ADDITIVE WEIGHTING METHOD IN DECISION SUPPORT SYSTEMS AT ISLAMIC BOARDING SCHOOL OF SYAICHONA MOH. CHOLIL GAMBUT - Muhammad Fajrian Noor; Syarifil Anwar; Sofyar Sofyar; Marjuatul Khairiah (UPT Publication and Journal Management, Islamic University of Kalimantan, 2023)
At Syaichona Moh. Cholil Islamic Boarding School Gambut is one of the events where students will be selected and have the right to be made outstanding students, usually called student stars. To simplify, it is necessary to create a decision support system (DSS). In the SPK selection of outstanding students, the Simple Additive Weighting (SAW) method was used. This method can determine the weight value for each criterion, followed by a ranking process to select the best alternative from all the alternatives. The student achievement data used is data from the test score of class 4 students at the MI level graduating in 2020. In the DSS test using the SAW method, it can be concluded that the highest score with a value of 0.90 is the value recommended by the user to determine outstanding students.